2019
DOI: 10.1002/adhm.201801465
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Prevention of Bacterial Infection and Enhanced Osteoinductivity of a Hybrid Coating with Selective Silver Toxicity

Abstract: mechanical properties and biocompatibility. However, despite the dramatic improvements in implant design and perioperative management over the past decades, implant-related infection and limited longevity remain challenges for surgeons and materials scientists. In the United States, 4.3% of orthopedic implants are reported as being infected, with the annual cost of implant-related infection being expected to exceed $1.62 billion by 2020. [1] Implant-related infection comprises a complex biological process incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 48 publications
1
51
0
1
Order By: Relevance
“…In addition, the coating can significantly stimulate osteogenic differentiation of MC3T3-E1 cells and promotes bone-implant osseointegration in vivo. Therefore, the hybrid coating exhibits antibacterial properties as well as allowing bone-implant osseointegration, thereby providing insights into the design of multifunctional implants for long-term orthopedic applications [97].…”
Section: Nanomaterials With Unique Features As Potential Weapons Tmentioning
confidence: 99%
“…In addition, the coating can significantly stimulate osteogenic differentiation of MC3T3-E1 cells and promotes bone-implant osseointegration in vivo. Therefore, the hybrid coating exhibits antibacterial properties as well as allowing bone-implant osseointegration, thereby providing insights into the design of multifunctional implants for long-term orthopedic applications [97].…”
Section: Nanomaterials With Unique Features As Potential Weapons Tmentioning
confidence: 99%
“…The following functionalization strategies have already been applied to increase antibacterial potential: drug-loaded surfaces [ 10 ], silver-implanted surfaces [ 11 ], polymer-functionalized surfaces [ 12 ], anodized/oxidized/ion-implanted surfaces [ 13 , 14 ], UV-activated surfaces [ 15 ], nanoscale surfaces [ 16 ], etc. A systematic review by J. Grischke et al concluded that highly modified surfaces enhance antimicrobial activity compared to that of commercial, pure titanium [ 8 ], but some research proved the significant cell toxicity of these surfaces [ 17 , 18 ], which limits the clinical application of new surfaces. Despite biocompatibility and effectiveness, production simplicity and adequate final cost are required for mass-production implants.…”
Section: Introductionmentioning
confidence: 99%
“…[50,[165][166][167][168] The dual chelating effect of PDA and chitosan has been demonstrated to significantly reduce Ag ion release with excellent antibacterial effect toward S. aureus, S. epidermidis, and E. coli (Figure 12). [171] The pH level at the peri-implant during bacterial infection is reduced to as low as 5.5. A pH-sensitive coating consisting of AgNPs and acetal linker has been fabricated and the Ag ion is released at low pH when bacterial infection occurs.…”
Section: Ag-incorporated Coatingmentioning
confidence: 99%